Searching for the odderon in ultraperipheral proton-ion collisions at the LHC - Harland-Lang, LA; Khoze, VA; Martin, AD; Ryskin, MG (American Physical Society, 2019)
We explore the possibility of observing odderon exchange in proton-ion collisions at the LHC, via the ultraperipheral photoproduction of C-even mesons. As well as the signal, we consider in detail the principle backgrounds, due to QCD-initiated production (i.e., double pomeron exchange) and γγ fusion. We find that while the photon-initiated background is dominant at very small momentum transfer, this can be effectively removed by placing a reasonable cut on the transverse momentum of the produced meson. In the case of QCD-initiated production, we show this is in general strongly suppressed by the small probability of no additional particle production in the central detector, namely the survival factor. In some scenarios, this suppression is sufficient to permit the observation of odderon exchange in Pb-p collisions in a clean environment, or else to place bounds on this. We in addition identify the cases of π0 and η(548) production as particularly promising channels. Here, the QCD-initiated background is absent for π0 due to isospin conservation and very small for η(548) due to its dominantly flavor octet nature and odd parity.